Simple for Dead Load--Continuous for Live Load Steel Bridge Systems - Azizinamini, Atorod (Engineering Journal, 2014)
This paper presents the development of design, fabrication, erection and construction procedures for a new steel bridge system referred to as simple for dead and continuous for live loads (SDCL). The economy of the SDCL system depends on several factors, including the use of economical and efficient details over the interior supports. Extensive experimental, numerical and analytical work was conducted to develop economical details and efficient ways of using the SDCL steel bridge system for straight and minimally skewed bridges in which the skew angle is less than 10Â°. Several bridges were then designed using the research results and their performance from the time of fabrication to construction and their long term behavior were studied. This knowledge was then used to provide detailed information on design, fabrication, erection, and construction procedures for steel bridges using the SDCL system. This paper provides a summary of the entire work, including design recommendations and economical details to be employed in conjunction with the SDCL steel bridge system.